The Filipino a century hence : a study on Filipino identity and the Philippine centennial coverage of the Philippine Daily Inquirer and Sunday Inquirer magazine from March to June 1998 - Expression, Wrigley N.; Fajardo, Maria Juanita S.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This study, on the whole, aims to understand the complexity of the Filipino identity. For this purpose, the researchers qualitatively analyzed the Philippine Centennial Celebration (PCC) issues of the Philippine Daily Inquirer and Sunday Inquirer Magazine. A total of 106 PDI articles from tis 100-Day Countdown to the Centennial (from March 04-June 12 and 13, 1998) and 80 SIM articles (March-June issues) were thoroughly studied and analyzed by the researchers using Dr. Maria Luisa Canieso Doronila's Set of Orientations in Defining National Identity as a basis. Dr. Doronila's four major value patterns and 16 orientations in national identity definition provided the operationalization of analysis in this study. The value patterns proved to be measurable and comprehensible. In the analysis of the samples, it turned out that Philippine Daily Inquirer came up with articles rated very satisfactory. This means that most of the PDI articles got three out of the four major value patterns in analysis and scoring. This rating was able to get 44.44% of the total number of PDI articles studied. Sunday Inquirer Magazine, meanwhile, had most of its articles rated good. The rating good means that most of the SIM articles got only one value pattern out of the four. However, reading and analysis of these articles will reveal that much of SIM got this rating because it focused more deeply on its topics and developed more on them. The rating good was able to get 47.5% of the total number of SIM articles. Having these results, the average rating turned out to be satisfactory (the rating between very satisfactory and good). 30.6% of the total number of PDI and SIM articles combined fit in the rating satisfactory. Besides the analysis based on Dr. Doronila's studies, the researchers also interviewed five academicians and experts on national identity. These are Dr. Mario I. Miclat, Director of UP Sentro ng Wikang Filipino (SWF), Professor Dolly G.L. Mibolos, teacher of Filipino Nationalism and various history subjects at the UP Department of History, Dr. Prospero R. Covar, former chair of UP Department of Anthropology and former graduate studies adviser, Prof. Carolina "Bobbie" S. Malay, chair of the UP Department of Journalism, and Dr. Maria Luisa Canieso-Doronila, former UP vice-president for public affairs and consultant for the Education and Research Program (ERP) of UP Center for Integrative and Development Studies from whom came the basis for the analysis in this study. Essential to the study also are interviews with Philippine Daily Inquirer Letty Jimenez-Magsanoc and Sunday Inquirer Magazine editorial staff headed by EIC and publisher Karla Delgado-Yulo. These eleven interviewees have warring opinions regarding the Filipino image and identity and how media treated it during the centennial. However, their differing views on the topic provided a rich ground for a well-argued, multi-sided debate on the real complex. and colorful character of the Filipino. For clarification, it is worthy to note that these experts do not argue about what the Filipino national identity is but how the mass media, particularly Philippine Daily Inquirer and Sunday Inquirer Magazine, should treat the subject regardless of time (whether before, during, and after the period covered in this research). In other words, the depth was added in the dimension of evaluation, not only volume and intensity, and became the central point of their debate. Speaking from the academician's point of view, Dr. Prospero R. Covar, Dr. Mario I. Miclat, Dr. Ma. Luisa C. Doronila, and Prof. Dolly G.L. Mibolos believe that mass media has not been critical of its role and function in promoting the Filipino sense of identity. They also argue that mass media is unmindful of the messages and images it transmits to the "intelligent" Filipino audience, thus, insulting their taste and limiting their intellect. The same also holds true, according to them, for PDI and SIM in their Philippine Centennial Celebration coverage. Although it is true that PDI and SIM gave due importance to the PCC, these experts unite in sayong that these two publications did so only on surface value. The coverage lack depth and proper emphasis of the positive image of the Filipino people and nation. From the media practitioners' pool, on the contrary, SIM staff and editors-in-chief Karla Delgado-Yulo (SIM) and Letty Jimenez-Magsanoc (PDI) counter claim that they really poured their best in projecting the Filipino and that they did so naturally because, as Filipino, they have all the reasons to do so. Their coverage, they say, should cater to Filipinos of various state, style, and orientation and comprehension levels. In a nutshell, these practitioners defend that a light and shallow treatment of the messages they transmit is a requirement for effective communication. Media, they think, should be 'as mababaw as possible' to be able to send the messages across to a great number of audience. Thus, it was a relief to find a neutral soldier in the war zone - Prof. Carolina S. Malay who is both a member of the academe and a mass media practitioner and analyst. She maintains that a thorough understanding if the unique features of mass media and the real nature of the audience is necessary. A healthy balance between the shallowness of message for greater understanding of a large audience and depth in the treatment of the message content is possible. After a thorough qualitative analysis of the PDI and SIM articles using Dr. Doronila's set of parameters and orientations in defining national identity, the researchers conclude that here was indeed an agenda behind the coverage of the PCC - that is to protect a colorful, complex and multi-faceted Filipino - proud of his glorious, freedom-loving and freedom-fighting heritage and even prouder of his present as he crafts and weaves his own destiny.
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman
Keywords: National characteristics, Filipino; Mass media and nationalism -- Philippines